2020
DOI: 10.2196/16810
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain-Authenticated Sharing of Genomic and Clinical Outcomes Data of Patients With Cancer: A Prospective Cohort Study

Abstract: Background Efficiently sharing health data produced during standard care could dramatically accelerate progress in cancer treatments, but various barriers make this difficult. Not sharing these data to ensure patient privacy is at the cost of little to no learning from real-world data produced during cancer care. Furthermore, recent research has demonstrated a willingness of patients with cancer to share their treatment experiences to fuel research, despite potential risks to privacy. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…The platform facilitated access to genomic data by establishing a secure trading system through the use of tokens. Separately, Glicksberg and colleagues 70 conducted a prospective cohort study for dissemination of de-identified clinical and genomic data of patients with late-stage cancer and reported two key findings. The completeness of the electronic medical records extracted by the blockchain platform was comparable with registry reports, which allowed rapid dissemination of real-world data.…”
Section: Discussionmentioning
confidence: 99%
“…The platform facilitated access to genomic data by establishing a secure trading system through the use of tokens. Separately, Glicksberg and colleagues 70 conducted a prospective cohort study for dissemination of de-identified clinical and genomic data of patients with late-stage cancer and reported two key findings. The completeness of the electronic medical records extracted by the blockchain platform was comparable with registry reports, which allowed rapid dissemination of real-world data.…”
Section: Discussionmentioning
confidence: 99%
“…It has the potential to address interoperability challenges and has so far been proposed to address several security and privacy issues in a number of different applications in the biomedical sector [ 41 ], despite the inevitable tension with important data protection principles and individual rights, when considering the current state of the distributed technology [ 42 ]. Although this technology is still more associated with the financial area [ 43 ], nowadays, there are many pilot projects currently underway, such as FHIRChain [ 44 ], Cancer Gene Trust [ 45 ], and Zenome [ 46 ]. While the implementation of the blockchain technology in clinical routine can address critical issues related to privacy, legal compliance, avoiding fraud, and improving patient care in cases of remote or emergency monitoring, further production developments, detailed proof-of-concept applications, and research articles are crucial for this technology to move forward and be implemented in the biomedical field.…”
Section: Possible Solution Strategiesmentioning
confidence: 99%
“…By facilitating a scalable, trusted data sharing framework for collaborators, 26,27 particularly on the international stage, blockchain provides new opportunities for the orthopaedic research community to aggregate data, particularly where study populations are small, for instance in the study of rare congenital and genetic musculoskeletal diseases. Collaborative blockchain solutions may also facilitate a more networked global arthroplasty registry system.…”
Section: Global Big Data Orthopaedic Researchmentioning
confidence: 99%